Calendário Cósmico como contextualização para abordar tópicos de física nuclear no ensino médio - Silva, Júpiter Cirilo da Roza da (2019)
The study is based on the understanding that, in general, the topics of Nuclear Physics, as well as those of Astronomy, are little explored in the initial training courses of Physics teachers and relegated to the background when it comes to High School. In particular, the study is located in the field of Nuclear Physics at this level of schooling, which represents a theme close to social, economic, environmental and technological development of a country, and is therefore fundamental for the training of students. In addition, the study is based on the identification that young people have moved away from scientific careers, showing a lack of interest in learning science, which may be related to the way it is present in basic education, including unattractive methodologies and curricula. These findings led us to explore the didactic possibility of contemplating topics of Nuclear Physics in a contextualized way from the Cosmic Calendar proposed by Carl Sagan. In this direction and taking as reference a degree course in Physics as a form of operationalization of innovative didactic proposals, the present study sought to answer the following question: what is the feasibility of a didactic proposal that takes the Cosmic Calendar as a support of contextualization of the contents of Physics Nuclear present in high school? The aim is to make it possible for students to feel secure in terms of their specific contents and, at the same time, motivated to approach the subject with their future students. Thus, the general objective of the work is to analyze how physicist graduates welcome the association of Nuclear Physics with astronomical events as a teaching proposal aimed at improving their conceptual understanding, as well as a didactic possibility for their future professional practice. To do so, the study chose as a locus of research an initial training course for physics teachers and developed a didactic module to discuss such possibility. As well, it took as theoretical reference the discussions related to the process of contextualization in the teaching. The didactic module, supplemented by a supporting text, had as instruments of evaluation with the public investigated the use of pre-tests and post-tests and the conduction of semi-structured interviews. The results, presented in a different way for each instrument, were analyzed from the reference points of the Physics teaching area. In general, the results pointed out that the academics expanded their knowledge in the field of Nuclear Physics and expressed their acceptance and approval regarding the didactic proposal developed, suggesting possibilities for their use in High School. As an educational product resulting from the study, a support material for high school teachers was structured, containing the topics covered in the course with students and being made available on the program page and the eduCapes portal <http://educapes.capes.gov.br/handle/capes/432903>.